Neuron‐targeted caveolin‐1 improves neuromuscular function and extends survival in SOD1G93A mice. Issue 6 (20th March 2019) - Sawada, Atsushi; Wang, Shanshan; Jian, Minyu; Leem, Joseph; Wackerbarth, Jesse; Egawa, Junji; Schilling, Jan M.; Platoshyn, Oleksandr; Zemljic-Harpf, Alice; Roth, David M.; Patel, Hemal H.; Patel, Piyush M.; et al.
ABSTRACT: Interventions that preserve motor neurons or restore functional motor neuroplasticity may extend longevity in amyotrophic lateral sclerosis (ALS). Delivery of neurotrophins may potentially revive degenerating motor neurons, yet this approach is dependent on the proper subcellular localization of neurotrophin receptor (NTR) to plasmalemmal signaling microdomains, termed membrane/lipid rafts (MLRs). We previously showed that over‐expression of synapsin‐driven caveolin‐1 (Cav‐1) ( SynCav1 ) increases MLR localization of NTR [e.g ., receptor tyrosine kinase B (TrkB)], promotes hippocampal synaptic and neuroplasticity, and significantly improves learning and memory in aged mice. The present study crossed a SynCav1 transgene‐positive (SynCav1 + ) mouse with the mutant human superoxide dismutase glycine to alanine point mutation at amino acid 93 (hSOD1 G93A ) mouse model of ALS. When compared with hSOD1 G93A, hSOD1 G93A /SynCav1 + mice exhibited greater body weight and longer survival as well as better motor function. Microscopic analyses of hSOD1 G93A /SynCav1 + spinal cords revealed preserved spinal cord α‐motor neurons and preserved mitochondrial morphology. Moreover, hSOD1 G93A /SynCav1 + spinal cords contained more MLRs (cholera toxin subunit B positive) and MLR‐associated TrkB and Cav‐1 protein expression. These findings demonstrate that SynCav1 delays disease progression in a mouse model of ALS, potentially by preserving or restoring NTR expression and localization to MLRs.—Sawada, A., Wang, S., Jian, M., Leem, J., Wackerbarth, J., Egawa, J., Schilling, J. M., Platoshyn, O., Zemljic‐Harpf, A., Roth, D. M., Patel, H. H., Patel, P. M., Marsala, M., Head, B. P. Neuron‐targeted caveolin‐1 improves neuromuscular function and extends survival in SOD1 G93A mice. FASEB J. 33, 7545–7554 (2019). www.fasebj.org